Magnetic resonance imaging system for intraoperative margin assessment for DCIS and invasive breast cancer using the ClearSight™ system in breast‐conserving surgery—Results from a postmarketing study. Issue 3 (1st November 2021) - Thill, Marc; Szwarcfiter, Iris; Kelling, Katharina; van Haasteren, Viviane; Kolka, Eyal; Noelke, Josefa; Peles, Zachi; Papa, Moshe; Aulmann, Sebastian; Allweis, Tanir
Abstract: Background and objectives: Breast‐conserving surgery (BCS) is followed by reoperations in approximately 25%. Reoperations lead to an increased risk of infection and wound healing problems as well as a worse cosmetic outcome. Several technical approaches for an intraoperative margin assessment to decrease the reoperation rate are under evaluation, some of them are still experimental. Methods: A prospective single‐arm post‐marketing study with 60 patients undergoing BCS for ductal carcinoma in situ (DCIS) and invasive breast cancer was conducted. The specimen was intraoperatively examined by the ClearSight™ system, a mobile magnetic resonance imaging system that is based on a diffusion‐weighted imaging protocol. However, the results were blinded to the surgeon. Results: The ClearSight™ system was performed for both ductal and lobular breast cancer and DCIS, with a sensitivity of 0.80 (95% confidence interval [CI]: 0.44–0.96) and a specificity of 0.84 (95% CI 0.72–0.92), with an overall diagnostic accuracy of 80%. Conclusion: Had the ClearSight™ been known to the surgeon intraoperatively, the reoperation rate would have been reduced by 83% for invasive carcinoma, from 10% to 2%, and 50% for DCIS, from 30% to 15% reoperations. A trial designed to examine the impact on reoperation rates is currently ongoing.